An automatic verification method for software quality with real business data - TIAN Biao; CUI Wei; HUANG Hui; FENG Xiaolong (Dianxin kexue)
Performance tests help to verify whether a business cluster can meet its access scale requirements, but current tools have problems such as evaluating proper parameters and requiring manual inputs, low performance, and difficulty in automation. A comprehensive quantitative request rate control mechanism and concurrent design approach based on coroutines were proposed, in contrast to JMeter's reliance on threads and locks. Furthermore, an architecture design for its corresponding TaaS service and a process automation scheme were introduced. This scheme automatically perceives responses, adjusts access rates accordingly, and schedules additional server executions using real business data, significantly enhancing operational efficiency and result intuitiveness.